Metallothionein-3 is a multifunctional driver that modulates the development of sorafenib-resistant phenotype in hepatocellular carcinoma cells - Rodrigo, Miguel Angel Merlos; Michalkova, Hana; Jimenez, Ana Maria Jimenez; Petrlak, Frantisek; Do, Tomas; Sivak, Ladislav; Haddad, Yazan; Kubickova, Petra; de Los Rios, Vivian; Casal, J Ignacio; Serrano-Macia, Marina; Delgado, Teresa C; et al. (Biomarker research, 2024)
BACKGROUND & AIMS: Metallothionein-3 (hMT3) is a structurally unique member of the metallothioneins family of low-mass cysteine-rich proteins. hMT3 has poorly characterized functions, and its importance for hepatocellular carcinoma (HCC) cells has not yet been elucidated. Therefore, we investigated the molecular mechanisms driven by hMT3 with a special emphasis on susceptibility to sorafenib. METHODS: Intrinsically sorafenib-resistant (BCLC-3) and sensitive (Huh7) cells with or without up-regulated hMT3 were examined using cDNA microarray and methods aimed at mitochondrial flux, oxidative status, cell death, and cell cycle. In addition, in ovo/ex ovo chick chorioallantoic membrane (CAM) assays were conducted to determine a role of hMT3 in resistance to sorafenib and associated cancer hallmarks, such as angiogenesis and metastastic spread. Molecular aspects of hMT3-mediated induction of sorafenib-resistant phenotype were delineated using mass-spectrometry-based proteomics. RESULTS: The phenotype of sensitive HCC cells can be remodeled into sorafenib-resistant one via up-regulation of hMT3. hMT3 has a profound effect on mitochondrial respiration, glycolysis, and redox homeostasis. Proteomic analyses revealed a number of hMT3-affected biological pathways, including exocytosis, glycolysis, apoptosis, angiogenesis, and cellular stress, which drive resistance to sorafenib. CONCLUSIONS: hMT3 acts as a multifunctional driver capable of inducing sorafenib-resistant phenotype of HCC cells. Our data suggest that hMT3 and related pathways could serve as possible druggable targets to improve therapeutic outcomes in patients with sorafenib-resistant HCC.
Keywords: Sorafenib; Resistance; Hepatocellular carcinoma; Metallothionein-3